Literature Review: Stunting Prevention with Environmental and Nutrition in the Prenatal Period - Hari Prasetyo Umar; Yuly Peristiowati; Byba Melda Suhita; Indasah; Tri Retnoningsih; Ike Nurrochmawati (Universitas STRADA Indonesia, 2023)
Background: Stunting increases the global public health burden by contributing 45% of all under-five deaths. Children who experience stunting as a result of someone not getting the right amount of nutritional intake for a long period of time (chronic). Thus, stunting can actually be prevented with adequate nutritional intake, especially in the First 1000 Days of Life. The target set by the government through the 2020-2024 National Medium-Term Development Plan (RPJMN) is to reduce the percentage of stunting by 14%. Stunting prevention is more effective in the prenatal period where 80% before stunting occurs, When compared to chasing from stunting to non-stunting, the success is only 20%. Purpose: This study aims to analyze stunting prevention with enviroinmental and nutrition in the prenatal period. Methods: The method used in this study is to use a literature study with a search method, combine the results of research and analyze facts from several scientific sources that are accurate and valid. Results: The results showed that 69% of households defecated in open areas. hazard defecation behavior can cause environmental pollution due to the spread of pathogenic germs from the anus. The kinds of nutritions better consumted by prenatal are Moringa leaves, The Tubaramure Food, iron folic acids (IFA), lipid based nutritional supplements (LNS). Conclusion: The meal preparation, amount of food, energy intake, and protein intake to prevent stunting. We noted there are many kinds of nutrition and supplements such as food from Moringa leaves, Moringa leaf extract supplementation, Moringa powder, and blood-added tablets, IFA, iron and folic acid supplements (IFA), iron supplements, folic acid (IFA), and lipid supplements given to pregnant women can significantly prevent stunting in children. Continuous education and monthly monitoring of pregnant women diet during pregnancy classes at the Posyandu are suggested to prevent stunting in children.